Persistent hepatitis C viral replication despite priming of functional CD8+ T cells by combined therapy with a vaccine and a direct‐acting antiviral. Issue 5 (18th December 2015) - Callendret, Benoit; Eccleston, Heather B.; Satterfield, William; Capone, Stefania; Folgori, Antonella; Cortese, Riccardo; Nicosia, Alfredo; Walker, Christopher M.
Abstract : Exhaustion of antiviral CD8 + T cells contributes to persistence of hepatitis C viral (HCV) infection. This immune response has proved difficult to restore by therapeutic vaccination, even when HCV replication is suppressed using antiviral regimens containing type I interferon. Because immunomodulatory effects of type I interferon may be a factor in poor T‐cell priming, we undertook therapeutic vaccination in two chronically infected chimpanzees during treatment with a direct‐acting antiviral (DAA) targeting the HCV NS5b polymerase protein. Immunization with genetic vaccines encoding the HCV NS3‐NS5b nonstructural proteins during DAA treatment resulted in a multifunctional CD8 + T‐cell response. However, these antiviral CD8 + T cells did not prevent persistent replication of DAA‐resistant HCV variants that emerged during treatment. Most vaccine‐induced CD8 + T cells targeted class I epitopes that were not conserved in the circulating virus. Exhausted intrahepatic CD8 + T‐cell targeting‐conserved epitopes did not expand after vaccination, with a notable exception. A sustained, multifunctional CD8 + T‐cell response against at least one intact class I epitope was detected in blood after vaccination. Persistence of HCV was not due to mutational escape of this epitope. Instead, failure to control HCV replication was likely caused by localized exhaustion in the liver, where CD8 + T‐cell expression of the inhibitory receptor programmed cell death 1 increased 25‐fold compared with those in circulation. Conclusion: Treatment with a DAA during therapeutic vaccination provided transient control of HCV replication and a multifunctional T‐cell response, primarily against nonconserved class I epitopes; exhaustion of liver‐infiltrating CD8 + T cells that target conserved epitopes may not be averted when DAA therapy fails prematurely due to emergence of resistant HCV variants. (Hepatology 2016;63:1442‐1454)